A two-dimensional organic-inorganic lead calcium perovskite material and its preparation method

By preparing two-dimensional organic-inorganic lead titanium ore materials, the difficulties in structural adjustment of existing perovskite materials have been solved, the fine adjustment of photoelectric properties has been achieved, the luminous efficiency and color purity of white LEDs have been improved, and it is suitable for a variety of photoelectric applications.

CN118221721BActive Publication Date: 2025-07-22JINING UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410290884.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-14
Publication Date
2025-07-22
Estimated Expiration
2044-03-14

AI Technical Summary

Technical Problem

The existing organic-inorganic hybrid perovskite materials are difficult to achieve multiple functions in the structural dimension adjustment, resulting in poor changes in their optical and electrical properties, which makes it difficult to meet the needs of various optoelectronic applications.

Method used

By preparing two-dimensional organic-inorganic lead perovskite materials, a mixture of lead bromide, 1-cyclohexylpiperazine, hydrobromic acid, acetonitrile and hypophosphoric acid is carried out, rotary evaporation, constant temperature heating and cooling crystallization are carried out to form a stable crystal structure, remove impurities and adjust the structural size of the material.

Benefits of technology

It realizes the performance adjustment of the material at the molecular level, improves the photoelectric performance, especially the luminous efficiency and color purity of white LEDs, and achieves a high CIR index, which is suitable for a variety of photoelectric applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118221721B_ABST
    Figure CN118221721B_ABST
Patent Text Reader

Abstract

The present invention discloses a two-dimensional organic-inorganic lead perovskite material and a preparation method thereof in the technical field of optoelectronic materials, including Step 1: adding 1-cyclohexylpiperazine to a hydrobromic acid solution to obtain a first mixed solution, and subjecting the first mixed solution to rotary evaporation to obtain a white powder; Step 2: selecting lead bromide and the white powder obtained in Step 1 in a mass ratio of 1:2, adding acetonitrile, hypophosphorous acid and hydrobromic acid in a volume ratio of 3:1:1, and obtaining a second mixed solution after mixing; Step 3: subjecting the second mixed solution to constant-temperature heating, and the heating temperature is 80 °C; Step 4: cooling and crystallizing the second mixed solution, and filtering to obtain the two-dimensional organic-inorganic lead perovskite material, which is used to adjust the structural size of the existing organic-inorganic hybrid perovskite material at the molecular level, so as to finely adjust the material properties and realize different optoelectronic applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of optoelectronic materials, and specifically relates to a two-dimensional organic-inorganic lead perovskite material and a preparation method thereof. Background Art

[0002] Due to the special properties of optoelectronic materials, including significantly low ion migration and defect density. A notable feature is that the strategy involves larger organic amine spacers, alternately inserted into inorganic lead halide octahedral layers. This spacer layer effectively reduces ion migration, even at higher bias voltages, which is particularly advantageous for X-ray detection. However, simultaneously achieving multiple functions within this field remains a formidable challenge.

[0003] Organic-inorganic hybrid perovskite materials are regarded as innovative compounds and have received extensive attention due to their special semiconductor properties and wide applications in various fields such as solar cells, LEDs, X-ray detectors, lasers, sensors, memory devices, catalysis, flexible electronics, photodetectors, and optical modulators. Generally speaking, organic-inorganic hybrid perovskite materials exhibit obvious advantages in terms of structural dimensions. Adjusting the size of these hybrid perovskite materials from three-dimensional to zero-dimensional (0D) structures will lead to significant changes in their optical and electrical properties. Therefore, the structural dimensions of these organic-inorganic hybrid perovskite materials can be adjusted at the molecular level to finely tune their properties and achieve different optoelectronic applications. Summary of the Invention

[0004] The purpose of the present invention is to provide a two-dimensional organic-inorganic lead perovskite material and a preparation method thereof, in order to adjust the structural dimensions of existing organic-inorganic hybrid perovskite materials at the molecular level, thereby finely tuning the material properties and achieving different optoelectronic applications.

[0005] To achieve the above purpose, the technical solution of the present invention is as follows: A two-dimensional organic-inorganic lead perovskite material and a preparation method thereof, including lead bromide, 1-cyclohexylpiperazine, hydrobromic acid, acetonitrile, and hypophosphorous acid;

[0006] Step 1: Add 1-cyclohexylpiperazine to a hydrobromic acid solution to obtain a first mixed solution, and perform rotary evaporation on the first mixed solution to obtain a white powder;

[0007] Step 2: Select lead bromide and the white powder from Step 1 and mix them in a mass ratio of 1:2, add acetonitrile, hypophosphorous acid, and hydrobromic acid in a volume ratio of 3:1:1, and obtain a second mixed solution after mixing;

[0008] Step 3: Carry out constant-temperature heating on the second mixed solution, and the heating temperature is 80 degrees Celsius;

[0009] Step 4: Cool the second mixed solution for crystallization, and obtain the two-dimensional organic-inorganic lead perovskite material after filtration.

[0010] Further, after obtaining the white powder in Step 1, wash the powder with ethanol, and then perform a drying treatment on the powder.

[0011] Further, during the process of cooling the second mixed solution for crystallization in Step 4, the temperature of the second mixed solution drops to twenty-five degrees Celsius.

[0012] Further, the cooling rate for cooling the second mixed solution for crystallization in Step 4 is five degrees Celsius per minute.

[0013] Further, when performing the drying treatment on the powder in Step 1, the powder is in a vacuum state.

[0014] Further, the heating time in Step 3 is five days.

[0015] Further, during the process of obtaining the second mixed solution in Step 2, stir once every 30 seconds.

[0016] Further, during the stirring process in Step 2, heat is applied, and the heating temperature is less than eighty degrees Celsius.

[0017] The technical principle of the above solution is as follows: The two-dimensional organic-inorganic lead perovskite material produced by this solution can emit bright broadband yellow light, with a quantum yield of 30.3%. The fabricated white LED reaches a relatively high CIR index of 94.1, exceeding that of the white LEDs based on YAG:Ce 3+ in the market (CIR < 80);

[0018] In this solution, part of the impurities in the powder are removed by washing with ethanol and vacuum drying;

[0019] In this solution, by slowly cooling, a relatively stable structure can be formed inside the crystals of the final product to a certain extent, eliminating the stress inside the crystals and improving the quality of the final product;

[0020] In this solution, during the process of obtaining the second mixed solution, stirring and heating can accelerate the dissolution of solid particles in the solution;

[0021] In this solution, the structural dimensions of the existing organic-inorganic hybrid perovskite material are adjusted at the molecular level, thereby finely adjusting the material properties and realizing different optoelectronic applications.

[0022] The additional aspects and advantages of the present invention will be partially given in the following description, partially will become obvious from the following description, or be understood through the practice of the present invention. Description of the Drawings

[0023] Figure 1 This is a flowchart of the embodiments of the two-dimensional organic-inorganic lead calcium perovskite material and its preparation method of the present invention;

[0024] Figure 2 This is the CIE chromaticity coordinate diagram of [CYP]PbBr4 in the embodiments of the two-dimensional organic-inorganic lead calcium perovskite material and its preparation method of the present invention;

[0025] Figure 3 This is a sectional view of the device in the embodiments of the two-dimensional organic-inorganic lead calcium perovskite material and its preparation method of the present invention.

[0026] The reference numerals in the accompanying drawings of the specification include: housing 1, ultrasonic transmitter 2, semiconductor refrigeration sheet 3, ultrasonic sensor 4, temperature sensor 5. Detailed implementation manners

[0027] The following is a further detailed description through specific implementation manners:

[0028] Example 1

[0029] As shown in the Figure 1 accompanying drawings: A two-dimensional organic-inorganic lead calcium perovskite material and its preparation method, including lead bromide, 1-cyclohexylpiperazine, hydrobromic acid, acetonitrile, and hypophosphorous acid;

[0030] Step 1: Add 1-cyclohexylpiperazine to the hydrobromic acid solution to obtain a first mixed solution, and perform rotary evaporation on the first mixed solution to obtain a white powder;

[0031] Step 2: Select lead bromide and the white powder obtained in Step 1 in a mass ratio of 1:2, add acetonitrile, hypophosphorous acid, and hydrobromic acid in a volume ratio of 3:1:1, and obtain a second mixed solution after mixing;

[0032] Step 3: Carry out constant-temperature heating on the second mixed solution, and the heating temperature is 80 °C;

[0033] Step 4: Carry out cooling crystallization on the second mixed solution, and filter to obtain the two-dimensional organic-inorganic lead calcium perovskite material;

[0034] In this example, after obtaining the white powder in Step 1, the powder is washed with ethanol, and then the powder is dried;

[0035] In this example, during the process of cooling crystallization of the second mixed solution in Step 4, the temperature of the second mixed solution drops to 25 °C;

[0036] In this example, the cooling rate of the second mixed solution during cooling crystallization in Step 4 is 5 °C per minute;

[0037] In this embodiment, when the powder is dried in step 1, the powder is in a vacuum state;

[0038] In this embodiment, the heating time in step 3 is five days;

[0039] In this embodiment, during the process of obtaining the second mixed solution after mixing in step 2, stirring is performed every 30 seconds;

[0040] In this embodiment, during the stirring process in step 2, heating is performed, and the heating temperature is less than 80 degrees Celsius.

[0041] The specific implementation process is as follows: In this embodiment, experiments were conducted on the above method;

[0042] 1.1 Synthesis

[0043] 1.1.1 Synthesis of CYPBr2.

[0044] Synthesize CYPBr2. Add 1-cyclohexylpiperazine to hydrobromic acid solution to form a clear solution. Then perform rotary evaporation on the solution to form a white powder. The powder is washed with ethanol multiple times, dried under vacuum conditions, and then collected.

[0045] 1.1.2 Synthesis of [CYP]PbBr4.

[0046] Dissolve PbBr2 (1 mmol) and 1-cyclohexylpiperazine (2 mmol), and place the PbBr2 and 1-cyclohexylpiperazine mixture in a mixture of acetonitrile (3 mL), hypophosphorous acid (1 mL), and hydrobromic acid (1 mL). The resulting suspension is heated and continuously stirred to promote dissolution, and then placed in an oven at 80 °C. The mixture is heated at a constant temperature of 80 °C for 5 days, and then gradually cooled to room temperature at a controllable rate of 5 °C per minute. The resulting product consists of colorless bulk crystals, which are collected by filtration and characterized as [CYP]PbBr4 (C 10 H 22 N2PbBr4) using single-crystal X-ray diffraction. The room-temperature single-crystal data of [CYP]PbBr4 were obtained using a Bruker Apex II CCD diffractometer with Mo-Kα radiation. The crystal structure was solved by direct methods and refined using the SHELXTL-2018 program. Anisotropic thermal parameters were used to refine all non-hydrogen atoms. The hydrogen atoms in the organic compounds were refined using geometric location and isotropic refinement methods. The structure refinement parameters of [CYP]PbBr4. Table S1. The crystal data of [CYP]PbBr4.

[0047]

[0048] 1.2 Characterization

[0049] 1.21 Powder X-ray diffraction (PXRD) analysis was carried out using a Bruker D8 Advance powder X-ray diffractometer equipped with copper Kα radiation at 40 kV and 40 mA current. The diffraction patterns were obtained at room temperature with a scanning range of 5 ~ 50° (2θ) and a scanning rate of 1° / min. To generate the simulated powder profiles, crystallographic files from single-crystal X-ray diffraction studies were used with the assistance of Mercury software.

[0050] 1.2.2 Morphological observations were carried out using a Zeiss Merlin Compact scanning electron microscope (SEM).

[0051] 1.2.3 Thermogravimetric analysis (TGA) was performed using a Metrel TGA / SDTA 851 thermal analyzer. The thermal stability test was carried out under a continuous flow of nitrogen at a constant protection in the temperature range of 30 - 800 °C.

[0052] 1.2.4 The solid UV-visible absorption spectra of the powder samples were measured using a PE Lambda900 UV-Vis spectrophotometer. The measurements were carried out at room temperature in the wavelength range of 200 - 800 nm, using BaSO4 as a reference standard. Raman measurements of the powder samples were performed using Horiba Scientific Laboratories with an excitation wavelength of 365 nm.

[0053] 1.2.5 The characterization of the photoluminescence properties. PL spectral analysis was carried out using an Edinburgh FLS980 fluorescence spectrometer. The spectrometer was equipped with an integrating sphere to measure the photoluminescence quantum yield (PLQY). The PLQY was determined using the equation ZQE = IS / (ER*ES), where IS represents the emission spectrum of the luminescence of the sample, ER corresponds to the spectrum of the measured excitation light with an empty integrating sphere (without sample), and ES represents the excitation spectrum of the stimulated sample. The analysis was carried out using an Edinburgh FLS980 fluorescence spectrometer and a picosecond pulsed diode laser. The average lifetime was determined by exponential fitting. In addition, the corresponding CIE chromaticity coordinates were determined using the emission spectrum, as Figure 2 shown.

[0054] 1.3 Application properties

[0055] To fabricate an LED lamp, a 365 nm UV LED chip was combined with the yellow phosphor [CYP]PbBr4 and the commercial blue phosphor BaMgAl 10 O 17 :Eu 2+ Combined together. The yellow phosphor [CYP]PbBr4 and the blue phosphor BaMgAl 10 O 17 :Eu 2+Mix with epoxy resin and stir continuously for 10 min. Apply the resulting mixture to the surface of the UV-LED chip and cure it under vacuum conditions for 30 min. The optical properties of the prepared WLED were evaluated using a programmed temperature rise LED photoelectric analyzer equipped with an integrating sphere (instrument: HAAS-2000).

[0056] 1.4. Calculation of theoretical energy bands

[0057] Using single crystal data, the electronic band structure of the [CYP]PbBr4 compound was calculated using the Castep software. The density functional theory (DFT) was used to determine the total energy, and the Perdew-Burke-Ernzerhof (PBE) generalized gradient approximation was used to describe the ion core-electron interaction with the norm-conserving pseudopotential. Valence electrons such as C-2s 2 2p 2 , N-2s 2 2p 3 , H1s 1 , Pb-6s 2 6p 2 and Br-4s 2 4p 5 were considered in the calculation. The basis set included a cut-off energy of 320 eV, which determined the number of plane waves. The Monkhorst-Pack k-point sampling method was used for numerical integration of the Brillouin zone. All other calculation parameters used the default settings and convergence criteria of the CASTEP program.

[0058] Variation of the integrated emission intensity with the reciprocal of

[0059] The temperature can be fitted to the well-known Arrhenius equation:

[0060] I PL and I0 represent the integrated emission intensities at different temperatures (T) and 0 K, respectively. Ea is the exciton binding energy, and kB is the Boltzmann constant. To estimate the electron-phonon interaction coefficient, we calculated the temperature-dependent Huang-Rhys factor (S) based on the full width at half maximum (FWHM) using the following model.

[0061]

[0062] where S represents the Huang-Kun factor, photon is the phonon frequency, and k B is the Boltzmann constant

[0063] Example 2

[0064] As attached Figure 1As shown, the difference from Example 1 is that, in order to realize the above process, a device is also disclosed, including a shell 1, in which an ultrasonic transmitter 2, a semiconductor cooling sheet 3, a plurality of temperature sensors 5 and a plurality of ultrasonic sensors 4 are arranged, and a controller is also provided on the shell 1. The ultrasonic sensors 4 are used to collect the concentration information of the solution in the shell 1, and the temperature sensors 5 are used to collect the temperature information of the solution in the shell 1. The controller controls the operation of the ultrasonic transmitter 2 and the semiconductor cooling sheet 3 according to the concentration information.

[0065] The specific implementation process is as follows: when using the device, the intermediate mixed solution is mixed with acetonitrile, low phosphoric acid and hydrogenated acid to form a suspension, the suspension is poured into the housing 1, the device is started, and the ultrasonic sensor 4 collects concentration information at various locations of the suspension. Since the suspension is not uniform, the difference between the concentration information collected by the ultrasonic sensor 4 is large at this time. The controller controls the ultrasonic transmitter 2 to work and emit ultrasonic waves into the suspension. The ultrasonic waves produce a cavitation effect and stir the suspension. At the same time, the controller controls the semiconductor refrigeration sheet 3 to work and heat the suspension to promote the dissolution of solid matter in the suspension. When the difference between the concentration information at various locations of the suspension is less than the set value, the suspension is basically uniform and becomes a second mixed solution.

[0066] Then the controller controls the ultrasonic sensor 4 to stop working, controls the ultrasonic transmitter 2 to continue working, and controls the temperature sensor 5 to start working. The temperature sensor 5 continuously collects temperature information at various locations in the second mixed solution. When the average temperature information at various locations in the second mixed solution is greater than eighty degrees, the controller controls the semiconductor refrigeration sheet 3 to cool. When the average temperature at various locations in the second mixed solution is less than eighty degrees, the controller controls the semiconductor refrigeration sheet 3 to heat. Until the average temperature at various locations in the second mixed solution is equal to eighty degrees, the controller controls the ultrasonic transmitter 2 and the semiconductor refrigeration sheet 3 to stop working. Due to uneven heat transfer, the temperature of the second mixed solution near the housing 1 drops faster than that of the second mixed solution inside. When the difference in temperature information at various locations in the second mixed solution collected by the temperature sensor 5 is greater than a set value, the controller controls the ultrasonic transmitter 2 to work, stirs the second mixed solution, and when the temperature of the second mixed solution drops, controls the semiconductor refrigeration sheet 3 to work, and raises the temperature of the second mixed solution.

[0067] The arrangement of the ultrasonic transmitter 2, the semiconductor cooling sheet 3, the temperature sensors 5 and the ultrasonic sensors 4 of the device enables the device to judge the state of the suspension during the stirring process. During the stirring process, there is no need for an operator to monitor on site, thereby reducing manpower waste. After the suspension is stirred evenly, the second mixed solution can be continuously heated immediately, and during the heating process, uneven heating of the second mixed solution caused by uneven heat transfer can be avoided to a certain extent, thereby affecting subsequent cooling and crystallization.

[0068] The above are only embodiments of the present invention, and common general knowledge of specific structures and / or characteristics in the solution is not described in detail herein. It should be noted that for those skilled in the art, without departing from the structure of the present invention, several modifications and improvements can be made, and these should also be regarded as the protection scope of the present invention, and these will not affect the implementation effect of the present invention and the practicality of the patent. The protection scope required by this application shall be subject to the content of its claims, and the specific implementation manners and the like recorded in the specification can be used to interpret the content of the claims.

Claims

1. A two-dimensional organic-inorganic lead perovskite material, characterized in that: The molecular formula of the two-dimensional organic-inorganic lead perovskite material is [CYP]PbBr4, which belongs to the monoclinic system and has a space group of P21 / c; Unit cell parameters: the axis length a is the axis length b is the axis length c is the axial angle α is 90°, the axial angle β is 107.212(11)°, and the axial angle γ is 90°; the unit cell volume V is The number of molecules Z in the unit cell is 4.

2. The preparation method of the two-dimensional organic-inorganic lead perovskite material according to claim 1, wherein: Step 1: Add 1-cyclohexylpiperazine to the hydrobromic acid solution to obtain a first mixed solution. Rotate-evaporate the first mixed solution to obtain a white powder. Wash the powder with ethanol and then dry the powder. Step 2: Select lead bromide and the white powder from Step 1 in a mass ratio of 1:2, add acetonitrile, hypophosphorous acid, and hydrobromic acid in a volume ratio of 3:1:1, and obtain a second mixed solution after mixing. Step 3: Heat the second mixed solution at a constant temperature, and the heating temperature is 80 °C. Step 4: Cool the second mixed solution for crystallization, and filter to obtain the two-dimensional organic-inorganic lead perovskite material.

3. The preparation method of the two-dimensional organic-inorganic lead perovskite material according to claim 2, wherein: During the process of cooling the second mixed solution for crystallization in Step 4, the temperature of the second mixed solution drops to 25 °C.

4. The preparation method of the two-dimensional organic-inorganic lead perovskite material according to claim 3, characterized in that: In Step 4, the cooling rate for cooling the second mixed solution for crystallization is 5 °C per minute.

5. The preparation method of the two-dimensional organic-inorganic lead calcium perovskite material according to claim 4, wherein: When drying the powder in Step 1, the powder is in a vacuum state.

6. The preparation method of the two-dimensional organic-inorganic lead perovskite material according to claim 5, wherein: In Step 3, the heating time is five days.

7. The preparation method of the two-dimensional organic-inorganic lead perovskite material according to claim 6, characterized in that: During the process of obtaining the second mixed solution after mixing in Step 2, stir once every 30 seconds.

8. The preparation method of the two-dimensional organic-inorganic lead perovskite material according to claim 7, characterized in that: During the stirring process in Step 2, heat is applied, and the heating temperature is less than 80 °C.

Citation Information

Patent Citations

  • Perovskite crystal, circular polarization luminescent material thereof, preparation method and application

    CN116396242A

  • Preparation method for organic-inorganic hybrid perovskite thin film and preparation method for semi-transparent solar cell

    WO2023184626A1